Implementasi Algoritma Haversine Formula untuk Pencarian Lokasi Rumah Makan Halal Terdekat Di Kota Parapat Berasis Mobile - Wini Allika Fitriani; Ali Ikhwan; Muhammad Alda (Teknik Informatika Fakultas Ilmu Komputer, 2025)
Simalungun District Culture and Tourism Office is a government agency whose activities include paying attention to tourism spots, especially Muslim tourists, namely in terms of finding halal places to eat or culinary in Parapat City. The haversine formula algorithm is one of the algorithms in a geographic information system that is able to calculate the shortest distance from the initial location to the destination location. By implementing the haversine formula algorithm in a geographic information system, it can be used to search for the nearest halal food location in Parapat City from the user's location. This research aims to be able to assist the community in finding the nearest halal food location in Parapat City and it is hoped that the Simalungun Regency Culture and Tourism Office can also provide location data for halal food that is integrated with a mobile-based geographic information system.